1998
DOI: 10.1074/jbc.273.9.5300
|View full text |Cite
|
Sign up to set email alerts
|

Lysenin, a Novel Sphingomyelin-specific Binding Protein

Abstract: Lysenin, a novel 41-kDa protein purified from coelomic fluid of the earthworm Eisenia foetida, induced erythrocyte lysis. Preincubation of lysenin with vesicles containing sphingomyelin inhibited lysenin-induced hemolysis completely, whereas vesicles containing phospholipids other than sphingomyelin showed no inhibitory activity, suggesting that lysenin bound specifically to sphingomyelin on erythrocyte membranes. The specific binding of lysenin to sphingomyelin was confirmed by enzyme-linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
332
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 319 publications
(340 citation statements)
references
References 49 publications
(42 reference statements)
7
332
0
1
Order By: Relevance
“…that lysenin recognizes other properties of sphingomyelin-containing membranes. Previous studies have shown that the interaction of lysenin and sphingomyelin is affected by the presence of other lipids (23,24). The mixing of glycosphingolipid and sphingomyelin hinders the formation of clusters of sphingomyelin alone and inhibits the binding of lysenin (24).…”
Section: Lipid Polarity and Tight Junctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…that lysenin recognizes other properties of sphingomyelin-containing membranes. Previous studies have shown that the interaction of lysenin and sphingomyelin is affected by the presence of other lipids (23,24). The mixing of glycosphingolipid and sphingomyelin hinders the formation of clusters of sphingomyelin alone and inhibits the binding of lysenin (24).…”
Section: Lipid Polarity and Tight Junctionsmentioning
confidence: 99%
“…The mixing of glycosphingolipid and sphingomyelin hinders the formation of clusters of sphingomyelin alone and inhibits the binding of lysenin (24). We have previously shown that sphingomyelin/cholesterol liposomes were 10,000 times more effective than liposomes of sphingomyelin alone in inhibiting lysenin-induced hemolysis (23,25).…”
Section: Lipid Polarity and Tight Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysenin is reported as an SM-direct cytolysin purified from the earthworm (27), for which binding to SM causes poring of the plasma membrane and subsequent cell death (22, 23, 25). …”
Section: Mouse Lymphoid Cells Defective Of Sphingomyelin Synthasementioning
confidence: 99%
“…For sphingomyelin stain, we used lysenin which specifically binds to the sphingomyelin, anti-lysenin antiserum, Alexa Fluor 568 (diluted 1:1,000; Molecular Probes) were used [25,30]. For filipin stain, the sections were incubated with 50 g/ml filipin in 1% BSA in PBS for 2 hr at room temperature after blocking with 1% BSA in PBS for 1 hr.…”
Section: Animalsmentioning
confidence: 99%